The Burden of Morbidity, Associated Expenditure, and Life Satisfaction among Geriatric Population in Nepal - Shrestha, Marina Vaidya; Shrestha, Sunil Babu; Joshi, Sunil Kumar (Nepal Medical College Journal, 2025)
An increase in life expectancy has raised a concern about whether these extra added years are characterized by good health and independence or health problems and dependency on others for care. Maximum life satisfaction (LS) is necessary to have healthy aging. The current study aimed to analyze the morbidity burden, associated expenditure, and life satisfaction among elderly population. A cross-sectional study was conducted at four different Municipalities of Bhaktapur district from February 1 to Sep 31, 2023 after obtaining ethical approval from Institutional Review Committee. A total sample size was 212 elderly participants above 60 years were included in this study. Stratified sampling method was applied. The questionnaire consisted of: a) socio-demographic b) morbidity and treatment cost c) coping strategy d) life satisfaction (LISAT-11). Descriptive statistics, chi-square (χ2) test, T-test and Anova was applied. This study involved 212 elderly participants (median age 69), primarily female (56.1%) and mostly from privileged ethnic backgrounds (86.8%).This study highlighted gender disparities, income sources, health conditions, and healthcare costs. Chronic conditions were prevalent among females and illiterate individuals. Cardiovascular issues were common. Females used outpatient services more, while males were hospitalized. Health expenses were significant, mainly covered by insurance and personal savings. Life satisfaction varied based on demographics and lifestyle factors.The elderly population bears a burden of morbidity, marked by a notable presence of health conditions and diseases. This burden leads to considerable personal expenses on healthcare services, especially concerning medication costs. Despite the financial pressures from healthcare expenditures, older individuals exhibit diverse degrees of life satisfaction.